A Novel Approach Using Integrated Greywater Treatment System Applying Net Zero Wastewater Concept for Sustainable Urban Communities - Khattab, Mianda (AUC Knowledge Fountain, 2023)
We are blessed with endless resources that are naturally existing in our world and we fully rely-on without envisioning the bigger picture of what would happen if these resources came to an end, or how can we even ensure sustainable lives by regenerating or reusing or utilizing the naturally existing resources? The surrounding ecosystem, the land we live on, the air we breathe, the water we drink and use for cooking, laundry, shower, irrigation, and many other usages are examples of the resources that we, as global users, are taking for granted. It is a common knowledge that we are almost 8 billion people living in this world with approximately 6% annual global population growth rate; this is reflected into higher economic levels, more demand, more jobs and more need and reliance on the previously mentioned resources. Infrastructure sector is one of the fastest moving and highly impactful sectors with population growth, as more housings and near-by facilities and jobs are constructed. This leads to having higher density areas in capitals which are the center of services for every human need and high pressure on naturally existing resources like water, which is considered in risk of scarcity as announced by the UN. As a result, some countries are impacted with poor access to drinking water. Egypt is not an exception to the previously mentioned fact; it is the 3rd most populous country in Africa and the most populous country in the Arab world, which is witnessing around 4 million growths in population rates between newborns and urbanization each year. As much as this reflects advancements in economic levels, more job opportunities, and safer lives, it also reflects that there is a need to have more housing, services and facilities accommodating this growth. This all adds pressure on the existing resources that need to be properly and sustainably managed. Saying this, to respond to the population and urbanization rates, Egypt has a vision to increase its infrastructure by almost 9% by 2025, as mentioned in Egypt-Country Commercial Guide, while shifting styling into more sustainable and even smart idealized communities. These are ideas to solve the population accommodation concern, but what about the resources that if not properly managed and efficiently reused and utilized, they will come to scarcity and hence, jeopardize the availability of resources for future generations? Water use and optimization is a major focal point as committed by Egypt under the National Water Resource Strategy (2017-2037) addressing the national water related challenges for the next years while putting solutions proposals under 4 main pillars of developing water resources by desalination 2 and recycling, rationalizing water use, creating an enabling environment and lastly, enhancing water quality [1]. Egypt produces 16.4 billion cubic meter wastewater annually with 26.8% of which are sewage wastewater and 73.2% are agricultural waste [2]. Hence, Egypt has a 2030 vision for treated wastewater reuse with a division of agricultural expansion related cities and non- agricultural related ones including Cairo; the direction is to maximize the treated wastewater for non-potable uses to decrease the load on potable water [2]. The objective of this research is to study the effect of treating greywater using an in- series integration of sand filter and aquatic plants; the collected and treated greywater from the community is intended to be reused again in the community irrigation system and toilet flushing, and this is to be integrated with a community and occupants’ rating system. The study is covered under 2 main novel approaches: the first is through an in-series experimental integration of greywater treatment systems and the second is on integrating occupants’ rating system through Tarsheed-Community while adapting a C2C wastewater treatment approach to include both community rating standards and occupants’ rating standards with Net Zero Approaches Addition. For the experimental work, the greywater treatment in-series system study was covered under 5 main pilot scale experimental phases in which phase 1 covered the sand filter design by selecting the best sand granule size and sand depth; with output sand size of 0.8-1.2mm and sand depth of 65cm. Phase 2 is a buildup on phase 1 outputs intended for studying the best rate of filtration to operate the sand filters, rates of filtration 2 𝑚3/𝑚2/𝑑, 4 𝑚3/𝑚2/𝑑 and 6 𝑚3/𝑚2/𝑑 are studied; the phase conclusion is that 4 𝑚3/𝑚2/𝑑 is the best rate of filtration to operate the sand filter. Phase 3 is focused on integrating the aquatic hyacinth plants in series with the sand filters, it is split into three main sub-phases, 3.A is for 2 𝑚3/𝑚2/𝑑 vs different plant densities, 3.B is for 4 𝑚3/𝑚2/𝑑 vs different plant densities and 3.C is for 6 𝑚3/𝑚2/𝑑 vs different plant densities; the phase output is that with 4 𝑚3/𝑚2/𝑑, 3.5 𝑘𝑔/𝑚2 plant density is the best to use. Phase 4 focused on studying intermittent and continuous system operational hours under the best conditions outputs from the previous phases; phases 1 through 4 used synthetic greywater mix prepared in the lab. Phase 5 covered the full system continuous run using real greywater collected from the AUC faculty housing. Both phases 4 and 5 outputs concluded that the treated greywater either with synthetic lab mix or real collected greywater meet the Egyptian code of wastewater reuse for irrigation parameters levels (Category-A). 3 For Tarsheed-Community Rating System, a thorough research was held first by comparison and analysis of known global rating systems like LEED-Cities and Communities and Estidama Pearl Community, with a highlight on the gaps and applicability for local use, while also leveraging available and accessible tools and resources proposal in the framework. In addition, occupants’ related rating systems like Well and Fitwel were also studied for comparison while highlighting the gaps and community rating system integration possibilities. Lastly, Living Community Challenge (LCC) was studied as it is the first integrated community and occupants’ rating system; however, it is complicated and costly to use. Out of all the studied rating systems the highlighted gaps and opportunities were added into the newly proposed Tarsheed Community and Occupants’ integrated rating system with an inclusion of C2C wastewater treatment approach. This research is studied with alignment to the 3 main sustainability pillars of being environmentally friendly, socially acceptable, easy to implement and maintain, as well as economically viable.